Diques neptúnicos en el Cretácico del Penibético: aspectos genéticos y etapas de relleno. - Company, M.; Rebollo, M.; Serrano, F.; Tavera, J.M.; Vera, J.A.; González-donoso, J.M.; Linares, D.; Martín-algarra, Agustín (Cuadernos de Geología Ibérica, 1982)
Sin resumen